Incidence and Risk of High-grade Stomatitis with mTOR Inhibitors in Cancer Patients. (16th March 2015) - Shameem, Raji; Lacouture, Mario; Wu, Shenhong
Abstract : Background : Inhibitors of the mammalian target of rapamycin (mTOR) pathway including everolimus and temsirolimus have been used extensively in cancer patients. Their use is associated with stomatitis, an adverse event resulting in morbidity and treatment interruptions or discontinuation. This study was conducted to determine the overall incidence and risk of stomatitis in cancer patients treated with the mTOR inhibitors by a meta-analysis of randomized controlled clinical trials (RCTs). Patients and Methods : Databases from PubMed and abstracts presented at the American Society of Clinical Oncology annual meetings up to October 2013 were searched for relevant studies. Eligible studies included RCTs using everolimus and temsirolimus at approved doses in cancer patients. Summary incidences, relative risks (RR), and 95% confidence intervals (CI) were calculated using a random- or fixed-effects model depending on the heterogeneity of the included trials. Results : A total of 11 RCTs with 4, 752 patients (mTORs: 2, 725, controls: 2, 027) with a variety of solid tumors were included in the analysis. The incidences of all-grade (grade 1–4) and high-grade stomatitis (grade 3–4) were 33.5% (95% CI: 21.9–47.6%) and 4.1% (95% CI: 2.6–6.3%), respectively. The incidence of high-grade stomatitis significantly varied with tumor types ( p = .004), and mTOR inhibitors (temsirolimus vs. everolimus, p < .001). In comparison with controls, mTOR inhibitors significantly increased the risk for developing all-grade stomatitis (RR: 4.04, 95% CI: 3.13–5.22, p < .001) and high-grade stomatitis (RR: 8.84, 95% CI: 4.07–19.22, p < .001). Conclusions : The mTOR inhibitors everolimus and temsirolimus significantly increased the risk of high-grade stomatitis in cancer patients. Efforts towards the prevention, treatment, and identification of individuals at risk may allow for improved quality of life and consistent dosing.